Interpretable causal machine learning elucidates performance regulation via atomic Fe‑S synergistic pathways in Sulfidated zero‑valent Iron - Zimin Yan; Rupeng Wang; Zhiling Li; Tianyi Huang; Yunxia Zu; Xiaoxi Zeng; Di Cao; Bin Wu; Jun Huang; Shih-Hsin Ho; Aijie Wang (Water Research, 2026)

Metabolomics-based investigation of PFOS-induced molecular perturbations across multiple rat organs - Tzu-Hsin Yen; Sheng-Han Lee; Hao-Jan Liang; Zou-Xiao Huang; Chi-Tsung Chen; Christopher Li; Ching-Yu Lin (Environmental Toxicology and Pharmacology, 2026)

Sonofoam: An ultrasound-responsive foam for broad pleural coverage and sonoporation-enhanced drug delivery in pleurodesis - Hsin-Yi Lin; Wei-Chih Liao; Yun-Chieh Lin; Hsin-Chin Li; Min-Yu Tsou; Bo-Tai Cheng; Yu-Nan Huang; Ulziijargal Sukhbat; Chun-Yi Chiang; Chi-Fen Chuang; Zong-Han Hsieh; Chih-Yen Tu; et al. (Chemical Engineering Journal, 2026)

NeuProIO: A dual-action solid drug nanoparticle topical formulation for simultaneous intraocular pressure reduction and neuroprotection for glaucoma - Lei Xu; Mu Li; Lin Qi; Tzu-Chen Wang; Dong Liu; Vimalin Jeyalatha Mani; Hsin-Yin Chuang; Qingbo Yang; Ruipu Mu; Samira Mahdi; Da Huang; Honglan Shi; et al. (Chemical Engineering Journal, 2026)

Anti-cancer effects of Psoralea corylifolia: insights into cancer hallmarks - Pin-Rong Chen; Tz-Syuan Su; Kun-Che Chang; Chien-Chih Chiu; Shu-Pin Huang; Hsin-Chih Yeh; Shu-Chi Wang; Chia-Yang Li (Phytochemistry Reviews, 2026)

CuO/PVA-based ultra-low-volume oral H2S detection system to reveal tongue coating effects - Moumita Deb; Chang-Chuan Huang; Yen-Ming Lai; Chang-Ju Chu; Yu-Shan Lee; Chien-Ting Chen; William Lee; Hsin-Fei Meng; Li-Yin Chen; Olivier Soppera; Chao-Sung Lai; Ding-Han Wang; et al. (Chemical Engineering Journal, 2025)

Fire dynamics, fire generated pollutants, and acute health implications: A scaling law analysis of heavy-fuel-oil pool fires - Kuang-Chung Tsai; Li-Hsin Cheng; Chi-Fu Yeh; Tzu-Yan Tseng; Tzu-Ping Tseng; Li-Jen Huang; Shu-Hsing Yeh; Hui-Tsung Hsu; Ching-Ho Lin; Chin-Hsing Lai; Peter Brimblecombe; Ming-Jen Chen (Fuel, 2025)

The Impact of Administrative Districts and Urban Landscape on the Dispersal of Aedes aegypti via Genetic Differentiation - Chin‐Gi Huang; Yi‐Cheng Tseng; Tsung‐Han Yu; Hui‐Ching Cheng; Tsung‐Ju Tsai; Jou‐Hsin Ting; Hsin‐Yi Ho; Ya‐Zhe Lee; Yen‐Chieh Chiu; Yu‐Ting Huang; Ting‐Chun Shih; Hsiang‐Yu Hsiao; et al. (Molecular Ecology, 2025)
Mosquito‐borne diseases affect millions and cause numerous deaths annually. Effective vector control, which hinges on understanding their dispersal, is vital for reducing infection rates. Given the variability in study results, likely due to environmental and human factors, gathering local dispersal data is critical for targeted disease control. To analyse the spread and differentiation of Aedes aegypti in southern Taiwan, we established a dengue vector monitoring network in Southern Taiwan's cities. This network employed GPS‐equipped ovitraps to gather eggs that were subsequently hatched in the laboratory and genotyped using genome‐wide SNP markers. From 168 individuals, we identified 757,238 SNPs for detailed analysis. The estimated effective dispersal distance was 154 m (95% CI: 126–180 m), consistent with prior mark‐release‐recapture (MRR) estimates. We discovered that geographic isolation significantly influences genetic differentiation at larger scales, such as between cities, whereas its correlation with genetic distances is considerably weaker at smaller scales, like within cities. This is likely due to the urban landscape in Taiwan, characterised by narrow roads and densely packed buildings, which facilitates extensive dispersal of Ae. aegypti. In evaluating potential barriers to Ae. aegypti dispersal, we found that roads had no significant impact, whereas administrative districts accounted for 4.8% of the population differentiation ( p −4 ). Surprisingly, this variation aligns with the effects of district‐specific mosquito control measures implemented at the municipal level. These findings highlight the complex interplay between urban landscapes, administrative measures and Ae. aegypti dispersal, emphasising the need for implementing targeted control strategies that consider these local dynamics.

Biofilm formation comparison of Vibrio parahaemolyticus on stainless steel and polypropylene while minimizing environmental impacts and transfer to grouper fish fillets - Li-Ming Su; Rong-Tan Huang; Hsin-I Hsiao (International Journal of Food Microbiology, 2025)

Discovery of polyoxygenated briaranes from octocoral Briareum stechei - Yue-Wen Chuang; Wei-Chen Ting; Su-Ying Chien; Li-Guo Zheng; Chih-Yin Huang; Zhi-Hong Wen; Yu-Jen Wu; Junichi Tanaka; You-Ying Chen; Jui-Hsin Su; Ping-Jyun Sung (Phytochemistry Letters, 2024)

Investigating illicit drug hotspots and daily variations using sewer-network wastewater analysis - Hank Hui-Hsiang Lin; Ming-Chi Hsieh; Jennifer Ia Wen Wen Liu; Yu-Hsiang Wang; Shu-Jie Huang; En Lien; Li-Wei Huang; Pei-Te Chiueh; Hsin-Hsin Tung; Angela Yu-Chen Lin (Chemosphere, 2024)

Determination of 16 ultraviolet–absorbing compounds in marine invertebrates by using LC-USI-MS/MS coupled with QuEChERS - Yu-Fang Huang; Yan-Jun Liu; Kai-Chien Yang; Zi-Ying Li; Chia-Hsin Liu; Hsin-Chang Chen (Food Chemistry, 2024)

An optimization method for maintenance routing and scheduling in offshore wind farms based on chaotic quantum Harris hawks optimization - Ming-Wei Li; Yi-Zhang Lei; Zhong-Yi Yang; Hsin-Pou Huang; Wei-Chiang Hong (Ocean Engineering, 2024)

Insecticide resistance and characteristics of mutations related to target site insensitivity of diamondback moths in Taiwan - Chia-Che Chang; Shu-Mei Dai; Chien-Yu Chen; Li-Hsin Huang; Yu-Hsien Chen; Ju-Chun Hsu (Pesticide Biochemistry and Physiology, 2024)

Integrated multilevel investigation of photosynthesis revealed the algal response distinction to differentially charged nanoplastics - Saibo Liu; Jingheng Han; Linjie Yao; Huijun Li; Guorong Xin; Shih-Hsin Ho; Xiaochen Huang (Journal of Hazardous Materials, 2024)

The angiogenesis-modulating effects of coumarin-derivatives - Han-Ting Huang; Ching-Yuan Huang; Chih-Jou Lee; Bo-Jie Sun; Zong-Wei Jhang; Chi-Chung Wen; Yun-Hsin Wang; Tao-Sheng Li; Ching-Yuh Chern; Yau-Hung Chen (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2024)

Biophysical mechanisms underlying tefluthrin-induced modulation of gating changes and resurgent current generation in the human Nav1.4 channel - Hsing-Jung Lai; Ming-Jen Lee; Hsin-Wei Yu; Kuan-Wen Chen; Ke-Li Tsai; Pi-Chen Lin; Chiung-Wei Huang (Pesticide Biochemistry and Physiology, 2024)

Utilizing Numerical Models and GIS to Enhance Information Management for Oil Spill Emergency Response and Resource Allocation in the Taiwan Waters - Chi-Min Chiu; Laurence Zsu-Hsin Chuang; Wei-Liang Chuang; Li-Chung Wu; Ching-Jer Huang; Yinglong Joseph Zhang (Journal of Marine Science and Engineering, 2023)
This study aims to establish a comprehensive workflow for developing emergency response plans for both actual and scenario oil spill incidents in the Taiwan waters while addressing the resource allocation for oil spill containment as well. This workflow comprises two vital components. The first component involves the integration of numerical tools and observational data, which includes the incorporation of wind data from sources such as the National Centers for Environmental Prediction (NCEP) or meteorological stations. Additionally, it incorporates ocean current data simulated by the semi-implicit cross-scale hydroscience integrated system model (SCHISM) into the general NOAA operational modeling environment (GNOME) model, which is a new approach for this purpose. In order to assess the efficacy of this component, two distinct case studies were conducted. The first case study focused on an incident in a northern coastal area of Taiwan under open sea conditions, whereas the second case study examined an incident within a major commercial harbor in central Taiwan. The second component of this workflow involves creating oil risk maps by integrating the results from the first component with specific geographical factors into Google Earth. These oil risk maps serve multiple purposes. They offer real-time information to emergency response commanders regarding oil spill hazard prediction, and they also enable the effective development of emergency response strategies and disposal plans for potential oil spill incidents. This is achieved by generating risk maps for various scenarios using the approach outlined in the first component. Additionally, these maps assist in the assessment and planning of resource allocation for oil containment.

Corrigendum to: “Exposure to polystyrene microplastics impairs hippocampus-dependent learning and memory in mice” J. Hazard. Mater. 430 (2022) 128431 - Chiang-Wen Lee; Lee-Fen Hsu; I.-Lin Wu; Yung-Li Wang; Wei-Chen Chen; Yan-Jun Liu; Lu-Tang Yang; Chong-Lun Tan; Yueh-Hsia Luo; Chia-Ching Wang; Hui-Wen Chiu; Thomas Chung-Kuang Yang; et al. (Journal of Hazardous Materials, 2023)

HAI-1 is required for the novel role of FGFBP1 in maintenance of cell morphology and F-actin rearrangement in human keratinocytes - Dajun D. Lu; Nanxi Huang; Sheng-Wen A. Li; Jessica R. Fang; Chih-Hsin Lai; Jehng-Kang Wang; Khee-Siang Chan; Michael D. Johnson; Chen-Yong Lin (Human Cell, 2023)

Modelling chloroform in indoor swimming pool air and water: the influences of internal air circulation and occupants - Hui-Tsung Hsu; Ming-Jen Chen; Kuang-Chung Tsai; Li-Jen Huang; Ching-Ho Lin; Chin-Hsing Lai; Li-Hsin Cheng (Environmental Science and Pollution Research, 2023)

Recyclable nanocomposites for carbon dioxide fixation and membrane separation using waste polycarbonate - Ying-Chi Huang; Li-Fan Chen; Yu-Hsiang Huang; Chien-Chieh Hu; Chien-Hsin Wu; Ru-Jong Jeng (Chemical Engineering Journal, 2023)

Blocking Hepatoma-Derived Growth Factor Attenuates Vasospasm and Neuron Cell Apoptosis in Rats Subjected to Subarachnoid Hemorrhage - Chia-Li Chung; Chieh-Hsin Wu; Yu-Hua Huang; Shu-Chuan Wu; Chee-Yin Chai; Hung-Pei Tsai; Aij-Lie Kwan (Translational Stroke Research, 2022)
Subarachnoid hemorrhage (SAH) is an important subcategory of stroke due to its unacceptably high mortality rate as well as the severe complications it causes, such as cerebral vasospasm, neurological deficits, and cardiopulmonary abnormality. Hepatoma-derived growth factor (HDGF) is a growth factor related to normal development and is involved in liver development and regeneration. This study explored the relationship between SAH and HDGF. Sixty rats were divided into five groups (n = 12/group): (A) control group; (B) rHDGF ab only group [normal animals treated with 50 µM recombinant HDGF antibodies (rHDGF ab)]; (C) SAH group; (D) SAH + pre-rHDGF ab group (SAH animals pre-treated with 50 µM rHDGF ab into the subarachnoid space within 24 h before SAH); and (E) SAH + post-rHDGF ab group (SAH animals post-treated with 50 µM rHDGF ab into the subarachnoid space within 24 h after SAH). At 48 h after SAH, serum and cerebrospinal fluid (CSF) samples were collected to measure the levels of pro-inflammatory factors by ELISA, and rat cortex tissues were used to measure protein levels by western blot analysis. Immunofluorescence staining for Iba-1, GFAP, TUNEL, and NeuN was detected proliferation of microglia and astrocyte and apoptosis of neuron cells. Neurological outcome was assessed by ambulation and placing/stepping reflex responses. Morphology assay showed that pre-treatment and post-treatment with rHDGF ab attenuated vasospasm after SAH. SAH up-regulated the levels of TNF-α, IL-1β, and IL-6 in both the CSF and serum samples, and both pre- and post-treatment with rHDGF ab inhibited the up-regulation of these pro-inflammatory factors, except for the serum IL-6 levels. Western blot analysis demonstrated that SAH up-regulated pro-BDNF and NFκB protein levels, and both pre- and post-treatment with rHDGF ab significantly reduced the up-regulation. The result from immunofluorescence staining showed that SAH induced proliferation of microglia and astrocyte and apoptosis of neuron cells. Both pre- and post-treatment with rHDGF ab significantly attenuated proliferation of microglia and astrocyte and inhibited apoptosis of neuron cells. Furthermore, treatment with rHDGF ab significantly improved neurological outcome. Blocking HDGF attenuates neuron cell apoptosis and vasospasm through inhibiting inflammation in brain tissue at early phase after SAH.

Anti-Inflammatory and anti-proliferative oleanane-type triterpene glycosides from the vine of Momordica cochinchinensis - Hung-Tse Huang; Yu-Chi Lin; Li-Jie Zhang; Chia-Ching Liaw; Hsin-Yen Chen; Ming-Tung Hsueh; Yao-Haur Kuo (Natural Product Research, 2021)

Unraveling microbiomes associated with decomposition of needles of two Pinus species with contrasting fire-adaptive strategies - Hsin-Ni Liu; Tsai-Wen Hsu; Yi-Hung Wu; Chao-Li Huang (Biology and Fertility of Soils, 2021)

Molecular Imaging for Radiolabeling a PSMA-Targeted Long Circulating Peptide as a Theranostic Agent in Mice Bearing a Human Prostate Tumor - Ming-Hsin Li; Sheng-Nan Lo; Ming-Wei Chen; Wei-Lin Lo; Yuan-Ruei Huang; Shih-Ying Lee; Su-Jung Chen; Shih-Wei Lo; Shih-Ming Wang; Chih-Hsien Chang (Journal of Medical and Biological Engineering, 2021)

Clinical Efficacy of a New Robot-assisted Gait Training System for Acute Stroke Patients - Andy Chien; Fei-Chun Chang; Nai-Hsin Meng; Pei-Yu Yang; Ching Huang; Li-Wei Chou (Journal of Medical and Biological Engineering, 2021)
Purpose Robot-assisted gait rehabilitation has been proposed as a plausible supplementary rehabilitation strategy in stroke rehabilitation in the last decade. However, its exact benefit over traditional rehabilitation remain sparse and unclear. It is therefore the purpose of the current study to comparatively investigate the clinical benefits of the additional robot-assisted training in acute stroke patients compared to standard hospital rehabilitation alone. Methods Ninety acute stroke patients (< 3 month) were recruited. All participants received the standard hospital neurorehabilitation comprises 45–60 min sessions daily for 3 weeks. Sixty patients also received an additional 30 min of robot-assisted gait training with the HIWIN MRG-P100 gait training system after each of the standard neurorehabilitation session. Outcome measures included: 1. Berg Balance Scale (BBS); 2. Brunnstrom Stage; 3. Pittsburgh Sleep Quality Index and 4. Taiwanese Depression Questionnaire (TDQ) which were assessed pre-treatment and then after every five training sessions. Results Both groups demonstrated significant improvement pre- and post-treatment for the BBS (robotic group p = 0.023; control group p = 0.033) but no significant difference (p > 0.1) between the groups were found. However, the robotic training group had more participants demonstrating larger BBS points of improvement as well as greater Brunnstrom stage of improvement, when compared to the control group. No significant within and between group statistical differences (p > 0.3) were found for Pittsburgh Sleep Quality Index and Taiwanese Depression Questionnaire. Conclusion The addition of robotic gait training on top of standard hospital neurorehabilitation for acute stroke patients appear to produce a slightly greater improvement in clinical functional outcomes, which is not transferred to psychological status.

Synergistic effects of pazopanib and hyperthermia against uterine leiomyosarcoma growth mediated by downregulation of histone acetyltransferase 1 - Chiao-Yun Lin; Angel Chao; Ren-Chin Wu; Li-Yu Lee; Shir-Hwa Ueng; Chia-Lung Tsai; Yun-Shien Lee; Meng-Ting Peng; Lan-Yan Yang; Huei-Jean Huang; Hsin-Shih Wang; Chyong-Huey Lai (Journal of Molecular Medicine, 2020)

Targeting Inflammation, PHA-767491 Shows a Broad Spectrum in Protein Aggregation Diseases - Yu-Han Chung; Chia-Wei Lin; Hsin-Yu Huang; Shu-Ling Chen; Hei-Jen Huang; Ying-Chieh Sun; Guan-Chiun Lee; Guey-Jen Lee-Chen; Ya-Ching Chang; Hsiu Mei Hsieh-Li (Journal of Molecular Neuroscience, 2020)

PARK14 (D331Y) PLA2G6 Causes Early-Onset Degeneration of Substantia Nigra Dopaminergic Neurons by Inducing Mitochondrial Dysfunction, ER Stress, Mitophagy Impairment and Transcriptional Dysregulation in a Knockin Mouse Model - Ching-Chi Chiu; Chin-Song Lu; Yi-Hsin Weng; Ying-Ling Chen; Ying-Zu Huang; Rou-Shayn Chen; Yi-Chuan Cheng; Yin-Cheng Huang; Yu-Chuan Liu; Szu-Chia Lai; Kun-Jun Lin; Yan-Wei Lin; et al. (Molecular Neurobiology, 2019)

Chronic low dose of AM404 ameliorates the cognitive impairment and pathological features in hyperglycemic 3xTg-AD mice - Hei-Jen Huang; Shu-Ling Chen; Hsin-Yu Huang; Ying-Chieh Sun; Guan-Chiun Lee; Guey-Jen Lee-Chen; Hsiu Mei Hsieh-Li; Ming-Tsan Su (Psychopharmacology, 2019)

Molecular surveillance of Vittaforma-like microsporidia by a small-volume procedure in drinking water source in Taiwan: evidence for diverse and emergent pathogens - Jung-Sheng Chen; Bing-Mu Hsu; Hsin-Chi Tsai; Yu-Pin Chen; Tung-Yi Huang; Kuan-Ying Li; Dar-Der Ji; Herng-Sheng Lee (Environmental Science and Pollution Research, 2018)

Mevastatin promotes neuronal survival against Aβ-induced neurotoxicity through AMPK activation - Edy Kornelius; Hsin-Hua Li; Chiung-Huei Peng; Hui-Wen Hsiao; Yi-Sun Yang; Chien-Ning Huang; Chih-Li Lin (Metabolic Brain Disease, 2017)

Suppressive effect of microRNA319 expression on rice plant height - Wei-Ting Liu; Peng-Wen Chen; Li-Chi Chen; Chia-Chun Yang; Shu-Yun Chen; GuanFu Huang; Tzu Che Lin; Hsin-Mei Ku; Jeremy J. W. Chen (Theoretical and Applied Genetics, 2017)

Role of Rhizophagus irregularis in alleviating cadmium toxicity via improving the growth, micro- and macroelements uptake in Phragmites australis - Li Wang; Xiaochen Huang; Fang Ma; Shih-Hsin Ho; Jieting Wu; Shishu Zhu (Environmental Science and Pollution Research, 2017)

Dormant season fertigation promotes photosynthesis, growth, and flowering of ‘Blueshower’ rabbiteye blueberry in warm climates - Shun-Hsin Huang; Kuo-Tan Li (Horticulture, Environment, and Biotechnology, 2015)

Do organophosphate-based traps reduce control efficiency of resistant tephritid flies? - Ju-Chun Hsu; Li-Hsin Huang; Hai-Tung Feng; Wen-Yin Su (Journal of Pest Science, 2015)

Interactions between household air pollution and GWAS-identified lung cancer susceptibility markers in the Female Lung Cancer Consortium in Asia (FLCCA) - H. Dean Hosgood; Minsun Song; Chao Agnes Hsiung; Zhihua Yin; Xiao-Ou Shu; Zhaoming Wang; Nilanjan Chatterjee; Wei Zheng; Neil Caporaso; Laurie Burdette; Meredith Yeager; Sonja I. Berndt; et al. (Human Genetics, 2015)

A consensus envelope protein domain III can induce neutralizing antibody responses against serotype 2 of dengue virus in non-human primates - Hsin-Wei Chen; Shih-Jen Liu; Yi-Shiuan Li; Hsueh-Hung Liu; Jy-Ping Tsai; Chen-Yi Chiang; Mei-Yu Chen; Chyi-Sing Hwang; Chin-Cheng Huang; Hui-Mei Hu; Han-Hsuan Chung; Sze-Hsien Wu; et al. (Archives of Virology, 2013)

Risk factors for primary lung cancer among never smokers by gender in a matched case–control study - Yen-Li Lo; Chin-Fu Hsiao; Gee-Chen Chang; Ying-Huang Tsai; Ming-Shyan Huang; Wu-Chou Su; Yuh-Min Chen; Che-Wei Hsin; Chin-Hao Chang; Pan-Chyr Yang; Chien-Jen Chen; Chao A. Hsiung (Cancer Causes & Control, 2013)

A new benzodioxocinone from the leaves of Cinnamomum tenuifolium - Hsin-Liang Chen; Soong-Yu Kuo; Yun-Ping Li; Ya-Fei Kang; Yu-Ting Yeh; Jin-Cherng Huang; Chung-Yi Chen (Natural Product Research, 2012)

Emerging threat of thrips-borne Melon yellow spot virus on melon and watermelon in Taiwan - Jui-Chu Peng; Shyi-Dong Yeh; Li-Hsin Huang; Ju-Ting Li; Yuan-Fu Cheng; Tsung-Chi Chen (European Journal of Plant Pathology, 2011)

β-Actin is a downstream effector of the PI3K/AKT signaling pathway in myeloma cells - Yen-Peng Ho; Chi-Wei Kuo; Yuan-Tong Hsu; Yu-Shan Huang; Li-Ping Yew; Wei-Feng Huang; Kuo-Chih Lin; Jung-Hsin Hsu (Molecular and Cellular Biochemistry, 2011)

Serological relationship between Melon yellow spot virus and Watermelon silver mottle virus and differential detection of the two viruses in cucurbits - Tsung-Chi Chen; Yun-Yueh Lu; Ying-Huey Cheng; Ju-Ting Li; Yi-Chun Yeh; Ya-Chi Kang; Chia-Peng Chang; Li-Hsin Huang; Jui-Chu Peng; Shyi-Dong Yeh (Archives of Virology, 2010)

Effects of the multiple polyadenylation signal AAUAAA on mRNA 3′-end formation and gene expression - Hsin-Hung Lin; Li-Fen Huang; Hsiao-Chien Su; Shih-Tong Jeng (Planta, 2009)

Lipopolysaccharide upregulates uPA, MMP-2 and MMP-9 via ERK1/2 signaling in H9c2 cardiomyoblast cells - Yi-Chang Cheng; Li-Mien Chen; Mu-Hsin Chang; Wei-Kung Chen; Fuu-Jen Tsai; Chang-Hai Tsai; Tung-Yuan Lai; Wei-Wen Kuo; Chih-Yang Huang; Chung-Jung Liu (Molecular and Cellular Biochemistry, 2009)

Spatiotemporal expression of zebrafish D-amino acid oxidase during early embryogenesis - Yau-Hung Chen; Wei-Li Chen; Yun-Hsin Wang; Mei-Yun Huang; Ming-Kai Chern (Fish Physiology and Biochemistry, 2007)

A G-Quadruplex Ligand 3,3′-Diethyloxadicarbocyanine Iodide Induces Mitochondrion-Mediated Apoptosis But Not Decrease of Telomerase Activity in Nasopharyngeal Carcinoma NPC-TW01 Cells - Chung-Pin Li; Jen-Hsin Huang; Ai-Chi Chang; Yi-Mei Hung; Chao-Hsiung Lin; Yee Chao; Shou-Dong Lee; Jacqueline Whang-Peng; Tze-Sing Huang (Pharmaceutical Research, 2004)